2000
DOI: 10.1136/bmj.321.7261.593
|View full text |Cite
|
Sign up to set email alerts
|

Costs and effectiveness of community postnatal support workers: randomised controlled trial

Abstract: Objectives To establish the relative cost effectiveness of postnatal support in the community in addition to the usual care provided by community midwives. Design Randomised controlled trial with six month follow up. Setting Recruitment in a university teaching hospital and care provided in women's homes. Participants 623 postnatal women allocated at random to intervention (311) or control (312) group. Intervention Up to 10 home visits in the first postnatal month of up to three hours duration by a community p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
199
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(206 citation statements)
references
References 17 publications
2
199
1
4
Order By: Relevance
“…8 However, offering support in addition to routine preventive visits has a limited impact on breastfeeding outcomes in developed countries. 12,13,[25][26][27] In contrast, our findings are in accordance with the results of prior observational studies showing that support provided by clinicians through specific ad- vice and practices during routine preventive visits is associated with higher exclusive breastfeeding rates and increased breastfeeding duration. 8,14 This study has broader clinical implications, in that it demonstrates that common barriers to breastfeeding support by primary care physicians during routine preventive visits can be resolved.…”
Section: Discussionsupporting
confidence: 91%
“…8 However, offering support in addition to routine preventive visits has a limited impact on breastfeeding outcomes in developed countries. 12,13,[25][26][27] In contrast, our findings are in accordance with the results of prior observational studies showing that support provided by clinicians through specific ad- vice and practices during routine preventive visits is associated with higher exclusive breastfeeding rates and increased breastfeeding duration. 8,14 This study has broader clinical implications, in that it demonstrates that common barriers to breastfeeding support by primary care physicians during routine preventive visits can be resolved.…”
Section: Discussionsupporting
confidence: 91%
“…Trials that used laypeople to deliver the intervention demonstrated a significant reduction in breastfeeding cessation at the time of the last study assessment (RR 0.86, 95% CI 0.76 to 0.98). 88,114,[354][355][356][357][358][359][360] Significant heterogeneity was present among these studies (I 2 = 75.6%). Further subgroup analysis did not reveal a statistically significant effect at any time point up to 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the studies of lay support that reported exclusive breastfeeding, there was a marked reduction in the cessation of exclusive breastfeeding before the last study assessment (RR 0.72, 95% CI 0.57 to 0.90). 114,355,356,[358][359][360] There was heterogeneity among these studies (I 2 = 96.3%). Further subgroup analysis indicated that this effect was significant within the first 3 months (RR before 4-6 six weeks 0.66, 95% 0.46 to 0.96; RR before 2 months 0.44, 95% CI 0.26 to 0.73; RR before 3 months 0.42, 95% CI 0.31 to 0.57)…”
Section: Discussionmentioning
confidence: 99%
“…Given the attached results of the trial of costs and benefits of the community postnatal support worker service 53 …”
Section: Appendixmentioning
confidence: 99%